PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) BERBANTUAN MEDIA KOMIK OTUBI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV SEKOLAH DASAR - Komah, Isti; Zulmi Roestika Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low mathematical problem-solving ability of fourth-grade elementary school students due to the limited use of innovative learning models and instructional media. The study aimed to determine the differences in students' problem-solving abilities and to examine the effect of the Think Pair Share (TPS) learning model assisted by Otubi comic media. This research employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The sample consisted of 50 fourth-grade students, including 25 students in the experimental class at SD Negeri Candirejo 01 and 25 students in the control class at SD Negeri Candirejo 02. Data were collected through tests, questionnaires, observations, and documentation, and analyzed using normality tests, homogeneity tests, the Independent Sample T-Test, and simple linear regression. The results showed that the experimental class achieved a higher posttest mean score (81.40) than the control class (77.20). The Independent Sample T-Test yielded a significance value of 0.023 (< 0.05), while the simple linear regression analysis showed a significance value of 0.001 (< 0.05). Therefore, the Think Pair Share (TPS) learning model assisted by Otubi comic media has a significant positive effect on students' mathematical problem-solving ability and can be used as an effective alternative in elementary mathematics learning.